TRANSFORMATIONS IN NANO-DIAMONDS WITH FORMATION OF NANO-POROUS SILICON CARBIDE AT HIGH PRESSURE - V. N. Kovalevsky; S. V. Grigoriev; А. E. Zhuk; A. V. Kovalevskay; I. F. Fomikhina (Наука и техника)
The paper contains investigations on regularities of diamond - silicon carbide composite structure formation at impact-wave excitation. It has been determined that while squeezing a porous blank containing Si (SiC) nano-diamond by explosive detonation products some processes are taking place such as diamond nano-particles consolidation, reverse diamond transition into graphite, fragments formation from silicon carbide. A method for obtaining high-porous composites with the presence of ultra-disperse diamond particles has been developed. Material with three-dimensional high-porous silicon-carbide structure has been received due to nano-diamond graphitation at impact wave transmission and plastic deformation. The paper reveals nano-diamonds inverse transformation into graphite and its subsequent interaction with the silicon accompanied by formation of silicon-carbide fragments with dimensions of up to 100 nm.